ВИЗНАЧЕННЯ ВЗАЄМНОГО РОЗТАШУВАННЯ УГРУПОВАННЯ КВАДРОКОПТЕРІВ ПІД ЧАС МОНІТОРИНГУ НАЗЕМНОЇ ОБСТАНОВКИ В НАДЗВИЧАЙНИХ СИТУАЦІЯХ - Якорнов, Євген Аркадійович; Цуканов, Олег Федорович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2020)
Determination of mutual location of the grouping of quadrocopters during monitoring of the territorial situation in emergency situations Methods for determining the coordinates of a group of quadrocopters in a ground-based control system for monitoring the situation in emergency response areas are presented.